LRP5-Mediated Lipid Uptake Modulates Osteogenic Differentiation of Bone Marrow Mesenchymal Stromal Cells - Lin, Jiachen; Zheng, Zhifa; Liu, Jieying; Yang, Guihua; Leng, Ling; Wang, Hai; Qiu, Guixing; Wu, Zhihong (Frontiers in Cell and Developmental Biology, 2021)
Nutritional microenvironment determines the specification of progenitor cells, and lipid availability was found to modulate osteogenesis in skeletal progenitors. Here, we investigated the implications of lipid scarcity in the osteogenic differentiation of bone marrow mesenchymal stromal cells (BMSCs) and the role of low-density lipoprotein receptor-related protein 5 (LRP5), a co-receptor transducing canonical Wnt/beta-catenin signals, in BMSC lipid uptake during osteogenesis. The osteogenic differentiation of murine BMSCs was suppressed by lipid scarcity and partially rescued by additional fatty acid treatment with oleate. The enhancement of osteogenesis by oleate was found to be dosage-dependent, along with the enhanced activation of beta-catenin and Wnt target genes. Conditional knockout (CKO) of Lrp5 gene in murine mesenchymal lineage using Lrp5fl/fl;Prrx1-cre mice led to decreased bone quality and altered fat distribution in vivo. After Lrp5 ablation using adenoviral Cre-recombinase, the accumulation of lipid droplets in BMSC cytoplasm was significantly reduced, and the osteogenesis of BMSCs was suppressed. Moreover, the impaired osteogenesis due to either lipid scarcity or Lrp5 ablation could be rescued by recombinant Wnt3a protein, indicating that the osteogenesis induced by Wnt/beta-catenin signaling was independent of LRP5-mediated lipid uptake. In conclusion, lipid scarcity suppresses BMSC osteogenic differentiation. LRP5 plays a role in the uptake of lipids in BMSCs and therefore mediates osteogenic specification.